2022
DOI: 10.1021/acsami.2c11201
|View full text |Cite
|
Sign up to set email alerts
|

Ni–O4 as Active Sites for Efficient Oxygen Evolution Reaction with Electronic Metal–Support Interactions

Abstract: Precise adjustment of the metal site structure in single-atom catalysts (SACs) plays a key role in addressing the oxygen evolution reaction (OER). Herein, we report the synthesis of O-doped Ni SACs anchored on porous graphene-like carbon (Ni–O–G) using molten salts (ZnCl2 and NaCl) as templates, in which the unique Ni–O4 structure serves as the active sites. Ni–O–G, with an overpotential of only 238 mV (@ 10 mA cm–2), is one of the more advanced catalysts. An array of characterizations and density functional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…37 The four C atoms of the graphene are replaced by O atoms to simulate O doping and a Ni atom is positioned on the O-doped graphene (Ni–O 4 ) to model the SANi 5 -O-2DRGO. 31 The O atoms are sp 2 hybridized and form three coordinated covalent bonds with surrounding atoms. 38 The four O atoms are replaced by N atoms (Ni–N 4 ) to build SANi 5 -N-2DRGO.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…37 The four C atoms of the graphene are replaced by O atoms to simulate O doping and a Ni atom is positioned on the O-doped graphene (Ni–O 4 ) to model the SANi 5 -O-2DRGO. 31 The O atoms are sp 2 hybridized and form three coordinated covalent bonds with surrounding atoms. 38 The four O atoms are replaced by N atoms (Ni–N 4 ) to build SANi 5 -N-2DRGO.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the images of HAADF-STEM and the surface sweep energy dispersive spectroscopy (EDS) of the SANi 5 -O-2DRGO catalyst show a highly dispersive single Ni atom (Fig.1c-f).The atomic dispersion state and bonding conguration of Ni in SANi 5 -O-2DRGO are further investigated by the normalized Ni K-edge X-ray absorption ne structure (XAFS) and Fouriertransformed EXAFS (FT-EXAFS). The position of the Ni K-edge is related to the Ni valence state 31. As shown in Fig.2a,the Ni K-edge of SANi 5 -O-2DRGO lies between that of Ni foil and NiO, indicating the valence state of Ni in SANi 5 -O-2DRGO is between 0 and +2.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…15,16 Single-atom catalysts (SACs) have been considered to have broad prospects in catalysis owing to the maximized utilization of loaded metal atoms and the excellent catalytic activity. 17,18 Numerous studies have revealed the commendable catalytic ability of SACs for a series of reactions, such as the OER, [19][20][21] ORR, [22][23][24] hydrogen evolution reaction (HER), [25][26][27][28] nitrogen reduction reaction (NRR), 29,30 carbon dioxide reduction reaction (CO 2 RR), 31,32 etc. In order to acquire a SAC structure with sufficiently dispersed transition metal (TM) atoms, a suitable substrate is firstly required, which should restrain the aggregation of loaded TM atoms.…”
Section: Introductionmentioning
confidence: 99%